Coping strategies of patients with end stage kidney disease on hemodialysis: a systematic review - Tan, Woei Ling; Lee, Khuan; Baharom, Anisah; Arshad, Mohd Mursyid (Jannetti Publications, 2021)
The purpose of this literature review was to explore the qualitative evidence on coping strategies used by patients with end stage kidney disease (ESKD) to manage the challenges and outcomes associated with the condition. A systematic review design following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines was used, and a thematic analysis was used to analyze the data. Four themes were identified from the 14 selected studies: external support, emotion management strategies, reliance on faith or spirituality, and self-care practices. Implications of these findings are discussed. Further primary qualitative studies using interviews and focus groups are needed to gain additional in-depth evidence of ESKD-related coping strategies.